Transforming Consumer Demand In The Age Of Digital Disruption: Evidence From Digital Ethnography (Netnography) And Islamic Economics - Anwar Syarif; Herman Syafii; Titi Inri Ani Gea; Ira Damayanti Harahap; Muhammad Yusuf Harahap; Muhammad Ridwan (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2025)
The digital economy has changed how consumers make purchasing decisions. The growth of e-commerce, social media platforms, digital recommendations, and digital payment systems has made consumption more fast-paced and emotionally driven. This study explores changes in consumer demand in the digital economy from an Islamic economics perspective, focusing on ethical and welfare issues.This research uses a qualitative method through digital ethnography. Data were collected by observing publicly available consumer activities, such as comments, reviews, and shopping experiences on platforms like Shopee, Tokopedia, TikTok Shop, Instagram, and TikTok. The data were analyzed using thematic analysis.The results show that consumer demand is influenced by algorithms, promotional pressure, and easy payment systems such as e-wallets and Buy Now Pay Later (BNPL). These features encourage impulsive buying and reduce control over spending. Some consumers later realize the risk of overconsumption and financial problems.From an Islamic economics perspective, these patterns raise ethical concerns related to Maqāṣid al-Sharī‘ah, especially the protection of wealth and rational thinking. This study highlights the need for ethical digital platforms, better consumer awareness, and policies that support responsible digital consumption.